Turning Society into Graphs: Early 20th Century Statistical Undertakings in Shanxi Province - Bréard, Andrea; Christ, Stefan; Tang, Lina (Journal of the European Association for Chinese Studies, 2025)
While no census was ever successfully completed for all of China under the Republic, the poor province of Shanxi, ruled by warlord Yan Xishan, published new population statistics every year from 1919. The province's Statistical Office not only consistently collected various statistical data, it was also a pioneer with respect to graphical statistics. Why did Shanxi produce so many statistics? Who produced them, and for what purpose? How did they figure into the modernisation and state-building attempts by Yan Xishan? What can we learn about his concerns regarding the population from the collected statistical materials? How is statistical knowledge and information made visible in statistical diagrams, what meaning is created, and which arguments are made through visual semantics? To tackle these questions, we examine relevant actors and institutions, closely read Yan Xishan’s preface to the earliest population statistics published in Shanxi, and finally look at the statistics and graphics published there between 1919 and 1931. 民國時期，儘管民國政府未完成全國人口普查，但閻錫山治下的山西省不僅持續收集統計資料，更以圖形統計的實踐領先全國。本研究通過分析原始資料、圖表及閻錫山親撰序言，探究其統計機制、實施主體及政治意圖。我們發現其圖表設計存在實驗性和不確定性，且凸顯出鮮明的政治邏輯——通過視覺化手段，將資料轉化為直觀的治理工具。統計圖以視覺秩序重構龐雜資訊，既服務于人口管控與國家能力建設，亦成為閻錫山推行地方現代化的話語載體。